ANALISIS CADANGAN KARBON DI HUTAN MANGROVE DESA BAHOI - Ruth Polii; Johnny S. Tasirin; Semuel P. Ratag (Universitas Sam Ratulangi, 2018)
Bahoi Village has an area of mangrove forest which is estimated to be as large as 36 ha which is well preserved by its people. The use of mangrove forests that do not consider the ecological role of mangrove forests can be one of the biggest threats to their sustainability. This study aims to calculate the stored carbon stock and species dominance in the Bahoi Village mangrove vegetation. This research is expected to be a source of data and information on carbon reserves, tourism management, species conservation, or sustainable production in Bahoi Village. The research method is systematic plot sampling. There were 15 plots with 5 plots each in 3 different cover types namely residential, tourism trail, and open tourism areas. Analysis of carbon stocks used alometric equations, structure and composition used INP, the results shows that carbon reserves are mostly in Sonneratia alba (64.41 kg / ha), followed by Bruguiera cylindrica (44.54 kg / ha), Rhizophora mucronata (43.04 kg / ha), Bruguiera gymnorhiza (35.88 kg / ha), Ceriops tagal (28.77 kg / ha), and the lowest Rhizophora apiculata ( 16.80 kg / ha). The highest carbon stock is found in residential area (45,39 kg/ha) followed by tourism trail (36,59 kg/ha) and open tourism area (29,29 kg/ha). Keywords: Mangrove Forest, Carbon, Bahoi